2013
DOI: 10.1021/ma400855z
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental and Computational Study of the Substituent Effect on Micellar Behavior of γ-Substituted Thermoresponsive Amphiphilic Poly(ε-caprolactone)s

Abstract: The effect of the core substituent structure on the micellar behavior of thermoresponsive amphiphilic poly(εcaprolactone) diblock copolymer micelles was investigated through a combination of experimental and computational methods. The polycaprolactone (PCL) amphiphilic block copolymers used in this study consisted of a hydrophilic poly{γ-2-[2-(2-methoxyethoxy)ethoxy]ethoxy-ε-caprolactone} block, which also endowed the polymer with thermoresponsiveness, and various hydrophobic poly(γ-alkoxy-ε-caprolactone) bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 42 publications
0
60
2
Order By: Relevance
“…In the case of poly{γ‐2‐[2‐(2‐methoxyethoxy)ethoxy]ethoxy‐ε‐caprolactone}, the addition of the oligo ethylene glycol substituent has been shown to afford hydrophilicity as well as thermoresponsivity . This biodegradable and biocompatible polymer can be used as the hydrophilic block in amphiphilic block copolymers that will self‐assemble in aqueous environments to form micelles for drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of poly{γ‐2‐[2‐(2‐methoxyethoxy)ethoxy]ethoxy‐ε‐caprolactone}, the addition of the oligo ethylene glycol substituent has been shown to afford hydrophilicity as well as thermoresponsivity . This biodegradable and biocompatible polymer can be used as the hydrophilic block in amphiphilic block copolymers that will self‐assemble in aqueous environments to form micelles for drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MEEECL offers the additional advantage of biodegradability through hydrolysis. Although MEEECL has been shown to have thermoresponsivity, the tunability of the lower critical solution temperature (LCST) is highly dependent on the hydrophobic portion of the block copolymer . Depending on the polymer used for the hydrophobic portion of the amphiphilic block copolymer, the LCST is not always in an appropriate range for biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies from our group revealed that the interaction between the drug and the polymer is more important than the void volume core in determining the drug loading capacity. 32 Therefore we have synthesized two different hydrophobic pendent groups featuring amphiphilic diblock copolymers with a substantial amount of PCL.…”
Section: Resultsmentioning
confidence: 99%
“…The size of copolymer micelles for P1 and P2 are larger than the previously reported values for amphiphilic block copolymers containing hydrophobic γ-substituted poly(ε-caprolactone)s despite the comparable molecular weights and ratios between the hydrophilic and hydrophobic blocks. 32, 33 The larger hydrodynamic size is most likely due to the bulky substituents which could result in an increase of the volume of the hydrophobic core. The sizes of micelles in TEM (transmission electron microscope) images were smaller than those measured by DLS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to overcome these limitations, many reactive groups, like hydroxyl, 6, 7 carboxylic 6, 8 and amino groups, 9,10 have been introduced onto the PCL chain with the aim for regulating its physico-chemical and biological properties, such as hydrophilicity, biodegradation rate and bioadhesion. 17,18 In the later approach, two issues containing monomer purity and deprotection feasibility as prerequisites ensure a successful synthesis. 12,13 Compared to postpolymerization modification strategy, [14][15][16] functional PCL prepared from its corresponding caprolactone monomer has exhibited better control over the pendant group substitution.…”
Section: Introductionmentioning
confidence: 99%